Сказки русских писателей XIX века: [сказки русских писателей для детей] - А. Погорельский (Школьное чтение, 2021)
Экземпляры: ф.14 (20220630) / Инвентарный номер: 62364 / Цена: / Сис.шифр: 84(2Рос=411.2)5-4 / Авт.знак: С 42 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=411.2)5-45